Práticas docentes e (in)disciplina: desafios para a formação de professores - De Rossi, Paulo Rogério (2024)
The dissertation that follows is part of the Research Line Fundamentals of Education, of the Postgraduate Program in Education at the University of Passo Fundo (UPF). He has focus on addressing students’ behavioral issues and their relationship with educators and is guided by the following question: in what sense does teacher training that feeds pedagogical practice can become an anchor for us to think about (and deal with) the discipline and school indiscipline? The general objective of the dissertation is to analyze how the conception of education and the pedagogical stance that underlie teacher training They can enable better behavior management and reduce indiscipline. The study is based on research that, in terms of approaching the problem, is predominantly qualitative and, in terms of objective, it is descriptive-analytical, proceeding through through bibliographic and documentary analysis. The main references of the research are the works by Antunes (2008) and Vasconcellos (2009), authors who discuss discipline and indiscipline in the classroom, as well as works by Freire (2015, 2022) and Benincá (2010), which point to an education that leads to autonomy and humanization. We seek, in the first chapter of the investigation, understand and characterize discipline and indiscipline understanding the character formation of the first and the origin and impacts of the second in the educational environment. Having understood this, in the second chapter we raise the agenda to the factors that trigger this disposition towards the indiscipline of some students and that, at certain times, the entire work carried out by the teacher is unbalanced; however, it is not difficult understand that there are solutions that emerge from a humanizing education through which, when students and educators set themselves on the path to a humanized dialogue, achieve great results. To achieve this, as shown in the third chapter, the teacher must be well prepared, planned and have good training, both initial and continuing in service. It appears that, from then on, using good pedagogical practices, you can carrying out good behavior management and reducing unnecessary conflicts will be a consequence. It results, therefore, that all actors in the educational process create good relationships, leading these subjects to self-confidence. This framework generates respect and becomes suitable ground for discipline and learning that provide autonomous and humanizing. In short, the studies carried out point to a dialogical stance between educator and student who, through methodical rigor, brings dialogue alive and sensitivity, participation and respect for autonomy as the most effective way to promote formative discipline and to deal with indiscipline in the classroom.